Chemical management of sourgrass with mixture of herbicides in areas under no-tillage system - Calistro, Vinicius Matoso; Loro, Gustavo; dos Santos de Lima Junior, Izidro; Pontes de Melo, Elmo; Peres de Souza, Victor Luiz (Scientia Agraria Paranaensis, 2021)
The sourgrass [Digitaria insularis (L.) Fedde] is a native species of the Americas found in tropical and subtropical regions, the difficulty in controlling Digitaria insularis with the herbicide Glyphosate generates the need to use other herbicides for an adequate management of the species. Therefore, the objective of the present work was to evaluate whether mixtures of herbicides, such as glyphosate; 2,4-D and Cletodim interfere with the effectiveness of controlling bitter campuses. The experiment was carried out in Ponta Porã (Mato Grosso do Sul State), the experimental design was randomized blocks, where the Digitaria insularis specimens present in each plot had 3 to 5 tillers, with 30 to 40 cm in height, the treatments used were control without weeding, weeding control, 1,800 g ha-1 ai of glyphosate + 10 mL of mineral oil, 240 g ha-1 of ai of clethodim + 10 mL of mineral oil (MO), 670 g ha-1 of ai of 2,4-D + 10 mL of MO, 240 g ha-1 of ai of Cletodim + 1,800 g ha-1 of ai of glyphosate + 10 mL of MO, 240 g of ha-1 of ai of Cletodim + 670 g of ha-1 of ai of 2.4-D + 10 mL of MO, 240 g ha-1 of ai of Cletodim + 1,800 g ha-1 of ai of glyphosate + 670 g ha-1 of ai of 2.4-D + 10 mL of MO. A precision CO2 sprayer was used, equipped with AIXR 110015 fan-type simple flat jet nozzles. The evaluations were carried out at 7, 14, 21 and 28 days after application. for the control of sourgrass, the treatments 6 (240 g ha-1 of ai of cletodim + 1,680 g ha-1 of ai of glyphosate + 10 mL of mineral oil) and treatment 8 (240 g ha-1 of ai of clethodim + 1,680 g ha-1 of glyphosate ae + 806 g ha-1 of 2,4-D ae + 10 mL of mineral oil), respectively, with better scores in visual control.